Acquiring Knowledge over the Economist's Lifetime - Hendrik P. van Dalen (Tinbergen Institute, 1997)
In this paper the reading behaviour of economists is examined to see whether particular typesof knowledge - basic and applied - imply different investment patterns. As it turns out, thereading intensity of advanced theoretical and empirical literature declines with three to fourpercent per year of experience, although researchers and economists with a mathematicalbackground start with a higher initial stock of knowledge of this type of literature. Businessand government economists concentrate on applied literature and news magazines; a type ofliterature which is not frequently read by mathematical economists. However, themathematical economists catch up with their non-mathematical colleagues in 12 to 15 yearstime. Furthermore, the introduction of graduate schools in Dutch academia has not broughtabout a fundamental change in reading habits. The biggest factor in explaining the divergencein reading behaviour among economists remains the mathematical, c.q. econometricsbackground in undergraduate training.
Keywords: 330; Lernprozess; Ökonomen; Niederlande